Vortex-Wide Detection of Large Aspherical NAT Particles in the Arctic Winter 2011/12 Stratosphere - Woiwode, W.; Höpfner, M.; Bi, L.; Khosrawi, F.; Santee, M. L. (FID GEO, 2019)
Micron-sized HNO3-containing particles in polar stratospheric clouds are known to denitrify the polar winter stratosphere and support chemical ozone loss. We show that populations of nitric acid trihydrate (NAT) particles with volume-equivalent median radii of 3–7 μm can be detected vortex-wide by means of infrared limb sounding. Key for detection are the applied optical characteristics of highly aspherical particles consisting of the β-NAT phase. Spectroscopic signatures and ambient conditions of detected populations show that these particles play a key role in denitrification of the Arctic winter stratosphere. Complementary gas-phase HNO3 observations indicate collocated highly efficient HNO3 sequestration within days and are consistent with measured spectral signals of populations of large NAT particles. High amounts of condensed gas-phase equivalent HNO3 exceeding 10 ppbv and long persistence of detected populations, despite expected gravitational settling, imply that our understanding of the particles is incomplete.